Good Corporate Governance And Audit Quality On Corporate Social Responsibility Disclosure - Syifa Dinah Rafifah; Indar Khaerunnisa (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2025)
This study aims to examine the influence of Good Corporate Governance (GCG) and audit quality on Corporate Social Responsibility (CSR) disclosure in mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. GCG is measured through the proportion of independent commissioners, the number of board directors, and the audit committee size. Audit quality is proxied by whether the company is audited by a Big Four accounting firm. CSR disclosure is assessed using a disclosure index based on Global Reporting Initiative (GRI) standards. The research uses a quantitative approach with secondary data collected from annual reports, analyzed using multiple linear regression through SPSS version 20. The results show that neither GCG indicators nor audit quality have a significant effect on CSR disclosure, whether partially or simultaneously. Although some variables show positive relationships, the statistical tests do not confirm their significance. These findings indicate that CSR disclosure in the mining sector may be driven by other factors beyond governance structure and audit quality. The study suggests the need for a stronger integration of sustainability into governance frameworks and encourages future research to explore other influencing factors such as organizational culture or stakeholder engagement.